Vocational education and training and innovation : research readings - Dawe, Susan [Herausgeber] (My University, 2004)
"This book of readings was commissioned to enable a better understanding of the past, present and future role of the Australian vocational education and training (VET) sector in business innovation. This collection considers what the innovation process in business means for Australian workers and identifies the contributions of the VET system. International comparisons offer insights into those elements missing or under-emphasized in the current Australian innovation system. Finally, strategies to enable the VET sector to engage with business innovation are illustrated through examples." (ERIC)
Keywords: Berufsbildungspolitik; Bildungspolitik; Innovationsprozess; Australien